Sistem Demokrasi: Marketing Politik dan Jaminan Kebenaran Informasi - Heroe Poerwadi (Jurnal Studi Pemerintahan, 2011)
The style of liberal democratic system of individualism, was more apparent on the implementation of the Indonesia elections in 2009. Those could be observed by the implementation of multi-party system, direct election system, the value system of one person one vote and one value, and culminated in the determination of legislative candidates by majority vote. As the consequency of the system, more campaigns held by personal than the political parties occurred in election 2009. The implications of the pattern of liberal individualism, increasingly the candidates took most of political advertising as the mass campaign media, in streets, mass media and public places. Strategic businesses like in the real business marketing industry was used to promote the candidates and political parties as a media to get as many voter as possible. In fact the implementation was distorted, the candidate only presented their personal popularity, but not the program they had. Moreover, they placed more the image performance, position highly than the commitment and personal integrity. Additionally, considerable segmentation techniques was had more pay attention than doing communication with people.